SIMULATION THE WORKING OF THE MANIPULATOR IN THE SOFTWARE ENVIRONMENT TIA PORTAL V.15.1(NOTIFICATION 1) - MAIDAN, Pavlo; MAKARYSHKIN, Denys; MYKHAYLOVSKIY, Yuriy; ZOLOTENKO, Ella (Herald of Khmelnytskyi National University. Technical sciences, 2022)
It is known that manipulators with automatic and hand types of control are distinguished by the type of control system. In manipulators with an automatic type of control, the links of the executive mechanism are set in motion by servo drives operating according to a previously developed program. In manipulators with a hand control type, there is an operator who acts on the links of the control mechanism and drives the links of the executive mechanism. The paper presents the results of simulation the working of the manipulator with six degrees of freedom, performed in the software environment TIA PORTAL V.15.1. Namely, the first stage, creating technological objects used as digital doubles for starting stepper motors, which are installed in the design of the manipulator. The creation of technological objects will make it possible to check the correct operation of the manipulator in the test mode, to determine and program the necessary speeds and accelerations, to monitor and eliminate possible errors during start-up. To simplify the application of some technological functions that can be used together with the SIMATIC controller, the so-called Technology objects (TO) were used in the software environment TIA Portal. When using TO data, available functions are encapsulated and provided to the application developer for ease of access and convenient use in the application environment. In particular, in the area of «Motion control», such TOs are used to facilitate the control and processing of data from axes, additional motion control functions, as well as to support the developer in creating a specialized program with motion control functions. The first stage of simulation the working of the manipulator in the software environment TIA Portal was completed, namely the creation of technological objects of this manipulator, that is, the creation of digital doubles for three stepper motors of the type 28BYJ-48, which are used as drives for the task of moving the manipulator.